Efek Corporate Governance dalam Memoderasi Hubungan antara Funding Decision dan Dividen Policies Terhadap Nilai Perusahaan - Jernih Simanjuntak (IPM2KPE, 2023)
This study aims to examine the effect of the relationship between Funding Decisions and Dividend Policies on company value with Corporate Governance as a moderating variable in Manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The research method used is descriptive research using secondary data from manufacturing companies. The technique used was purposive sampling with a total sample of 106 companies. The results of the study explain that Funding Decisions have a positive and significant influence on Firm Value, Dividend Policies have a negative and significant influence on Firm Value, Corporate Governance has a positive and significant influence on Firm Value, Corporate Governance moderates the relationship between Dividend Policy on Firm Value and Corporate Governance moderates the relationship between Funding Decisions on Corporate Value. In conclusion, optimizing the value of the company is very important because increasing the value of the company means maximizing the company's main goals. Increasing the value of the company is an achievement that is in accordance with the wishes of the shareholders, because by increasing the value of the company, the welfare of the shareholders will also increase. Keywords: Corporate Governance, Dividend Policies, EVIEWS 9.0, Funding Decisions, Corporate Value